Resveratrol Promotes Diabetic Wound Healing via SIRT1-FOXO1-c-Myc Signaling Pathway-Mediated Angiogenesis - Huang, Xiaozhong; Sun, Jia; Chen, Gen; Niu, Chao; Wang, Ying; Zhao, Congcong; Sun, Jian; Huang, Huiya; Huang, Shuai; Liang, Yangzhi; Shen, Yingjie; Cong, Weitao; et al. (Frontiers in Pharmacology, 2019)
Background/Aims: Diabetic foot ulcers (DFUs) represent a serious challenge in clinical practice, in which the hyperglycemia-induced disturbance of angiogenesis and endothelial dysfunction play a crucial role. Resveratrol (RES), a potential agonist of silent information regulator 1 (SIRT1), can improve endothelial function and has strong pro-angiogenic properties, thus becoming a research focus for the treatment of DFUs; however, the underlying mechanism by which RES regulates these processes remains unclear. Therefore, we aimed to investigate whether RES exerts its protective role in diabetic wound healing by alleviating hyperglycemia-induced endothelial dysfunction and the disturbance of angiogenesis. Methods: We investigated the effects of RES on cell migration, proliferation, apoptosis, tube formation, and the underlying molecular mechanisms in high glucose (33 mM)-stimulated human umbilical vein endothelial cells (HUVECs) by semi-quantitative RT-PCR, western blot analysis, terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining, and immunofluorescence in vitro. We further explored the role of RES on endothelial dysfunction and wound healing disturbance in db/db mice by TUNEL staining, immunofluorescence, and photography in vivo. Results: We observed an obvious inhibition of hyperglycemia-triggered endothelial dysfunction and a disturbance of angiogenesis, followed by the promotion of diabetic wound healing via RES, along with restoration of the activity of the hyperglycemia-impaired SIRT1 signaling pathway. Pretreatment with EX-527, a SIRT1 inhibitor, abolished the RES-mediated endothelial protection and pro-angiogenesis action, and then delayed diabetic wound healing. Furthermore, examination of the overexpression of a transcription factor substrate of SIRT1, forkhead box O1 (FOXO1), in HUVECs and db/db mice revealed that RES activated SIRT1 to restore hyperglycemia-triggered endothelial dysfunction and disturbance of angiogenesis, followed by the promotion of diabetic wound healing in a c-Myc-dependent manner. Pretreatment with 10058-F4, a c-Myc inhibitor, repressed RES-mediated endothelial protection, angiogenesis, and diabetic wound healing. Conclusion: Our findings indicate that the positive role of RES in diabetic wound healing via its SIRT1-dependent endothelial protection and pro-angiogenic effects involves the inhibition of FOXO1 and the de-repression of c-Myc expression.